ASPECTS OF RESTORING THE EXTENT VILLAGE, TOWN AND CITY COUNCILS AND ADMINISTRATIVE‐TERRITORIAL UNITS FOR STATE LAND CADASTRE - Peresolyak, V. Y. (Землеустрій, кадастр і моніторинг земель, 2013)
The necessity of manufacturing electronic cadastral maps, plans, digital raster ‐ that meet modern requirements ‐ in order to restore the boundaries of village, town and city councils and boundaries of settlements for the state land cadastre.